Positive Impact of Organized Physical Exercise on Quality of Life and Fatigue in Children and Adolescents With Cancer - Spreafico, Filippo; Barretta, Francesco; Murelli, Michele; Chisari, Marco; Gattuso, Giovanna; Terenziani, Monica; Ferrari, Andrea; Veneroni, Laura; Meazza, Cristina; Massimino, Maura (Frontiers in Pediatrics, 2021)
Background: Cancer and its treatment can cause serious health issues that impair physical and mental wellbeing in children and adolescents. Exercise may be a valid strategy for managing some symptoms, including fatigue. In the light of our experience, we provide further justification for including exercise as part of routine childhood cancer care. Methods: Forty-four children and adolescents who had solid cancers not contraindicating their movement were invited to join an in-hospital 6-week supervised exercise program, and asked afterwards to complete validated quality of life and fatigue scales. The program consisted of personalized workout sessions of aerobic, resistance and flexibility exercises. The results obtained on the scales were compared between 21 patients who engaged in the exercise program (GYM group) and 23 who refused (No-GYM group), examining the different dimensions of health-related quality of life (physical, emotional, cognitive, social) and fatigue (general, sleep/rest, cognitive) in the two groups. Results: Being diagnosed with cancer initially prompted all but one of the respondents to drop -out of previous routine exercise or sports although their continuation had not been contraindicated. After 6 weeks of exercise, the GYM group’s scores for quality of life and fatigue showed a statistically significant better perceived emotional functioning, and a trend towards a better social functioning than in the No-GYM group. Conclusion: We suggest that exercise improves the satisfaction of children and adolescents with cancer with their physical, mental and social functioning. We emphasize the potential benefits of general practitioners recommending exercise for their young patients with cancer.